CIRCULAR ECONOMY BUSINESS MODELS: THE CRITICAL ROLE OF MARKETING IN SHAPING CONSUMER ACCEPTANCE AND BEHAVIOR - Arios Zeus Sandry; Lukmanul Hakim; Tibrani (RADJA PUBLIKA, 2026)
This study examines the role of marketing in influencing consumer acceptance and behavior within circular economy business models. While circular systems provide notable environmental and economic advantages, their effectiveness depends largely on consumers’ willingness to adopt new consumption patterns. The findings identify perceived value, trust, and awareness as key drivers of acceptance, while barriers such as ownership concerns, perceived risk, and unfamiliarity hinder adoption. The study highlights the importance of strategic marketing—through clear communication, storytelling, and value framing—in overcoming these challenges. It also emphasizes that consumer responses vary across demographic and cultural contexts, requiring targeted and adaptive approaches. Theoretically, this research integrates marketing principles with circular economy frameworks and proposes a conceptual model linking circular offerings, perceptual mediators, moderating factors, and behavioral outcomes. Practically, it offers insights for organizations implementing circular models, particularly the need to build trust, enhance value perception, and educate consumers. However, the study is limited by its conceptual nature and the evolving state of the field. Future research should focus on empirical validation, cross-cultural and longitudinal analysis, and the role of digital innovation in supporting circular adoption.